Factor structure and psychometric properties of the Inflexible Eating Questionnaire in a sample of adult women. (1st November 2019) - Linardon, Jake; Incerti, Lisa; McLean, Courtney
Abstract: The Inflexible Eating Questionnaire (IEQ) is a recently developed measure that assesses an individual's inflexible adherence to rigid eating rules, along with the tendency to respectively feel empowered or distressed when such rules are or are not followed. At present, evidence supporting the unidimensional structure and psychometric properties of the IEQ is limited to one specific sample of Portuguese adults. Establishing whether the IEQ is a valid and reliable measure in a different sample and by an independent research team is needed. We sought to examine the factor structure and psychometric properties of the IEQ in large sample ( n = 1000) of Australian female adults. A unidimensional structure was replicated and evidence of internal consistency (α = .89) was found. IEQ scores were significantly and moderately correlated with various eating restraint measures and intuitive eating, providing evidence of convergent validity. IEQ scores also predicted incremental variance in global eating disorder symptomatology and psychosocial impairment after controlling for intuitive eating, flexible control, and rigid dietary control. Present findings offer further support for the validity and reliability of the IEQ in a non-clinical sample of women. A brief measure that assesses the inflexible adherence to eating rules may be valuable for validating current models of eating disorder psychopathology. Furthermore, incorporating the IEQ into the assessment of future randomized trials of eating disorder prevention or treatment programs may be beneficial for elucidating these interventions mechanisms of change.